Auto-antibodies against the angiotensin II type I receptor in women with uteroplacental acute atherosis and preeclampsia at delivery and several years postpartum. (August 2018) - Rieber-Mohn, Amalie Bjerke; Sugulle, Meryam; Wallukat, Gerd; Alnæs-Katjavivi, Patji; Leite Størvold, Gro; Bolstad, Nils; Redman, Christopher WG; Dechend, Ralf; Staff, Anne Cathrine
Highlights: Higher rate of circulating AT1 -AA in preeclamptic than normotensive pregnancies. Uteroplacental acute atherosis is not correlated with maternal circulating AT1 -AA. Few women had circulating AT1 -AA years after pregnancy, with unknown CVD potential. Abstract: Background: Uteroplacental acute atherosis is a pregnancy-specific lesion resembling early stages of atherosclerosis found frequently in preeclampsia. Preeclampsia is associated with an increased risk for future maternal atherosclerotic cardiovascular disease. The renin-angiotensin-system plays a role both in atherosclerosis and in preeclampsia. Circulating agonistic autoantibodies at the angiotensin-II type 1 receptor (AT1 -AA) are increased in preeclampsia. We hypothesized an association between AT1 -AA at delivery and postpartum with acute atherosis in pregnancy. Material and Methods: Maternal serum and decidua basalis tissue was collected at elective cesarean section (n = 41; 24 preeclampsia, 17 normotensive controls). Circulating AT1 -AA were detected by a bioassay using spontaneously beating rat cardiomyocytes at delivery (n = 41) and 5–8 years postpartum in a subgroup (n = 10). Decidual acute atherosis was assessed by immunohistochemistry. Results: Significantly less normotensive controls (18%; 3/17) than women with preeclampsia (58%; 14/24) were AT1 -AA positive at delivery, p <0.01. Uteroplacental acute atherosis and circulating AT1 -AA at delivery were not significantly correlated. Postpartum, 2 prior preeclamptic women had circulating AT1 -AA, both without acute atherosis in pregnancy. Conclusions: Our results confirm that circulating AT1 -AA are present significantly more often in preeclampsia than in normotensive pregnancy, however without association to acute atherosis. Whether circulating maternal AT1 -AA or acute atherosis target young women at increased long-term cardiovascular risk warrants further investigations.